Assessment of the lifecycle carbon emission and energy consumption of lithium-ion power batteries recycling: A systematic review and meta-analysis. (15th August 2023) - Li, Jingjing; Li, Lanlan; Yang, Ranran; Jiao, Jianling
Abstract: Recycling spent lithium-ion batteries (LIBs) is necessary for environmental protection and the reuse of valuable resources. Previous studies have used the LCA method to evaluate the environmental and energy performance of single spent LIB recycling. However, lacking research can provide an overall view of the spent LIBs recycling. This study uses a systematic meta-analysis method to quantitatively analyze different independent research results. We draw the following conclusions. (1) The global warming potential (GWP) and cumulative energy demand (CED) of recycling 1 kg spent LIBs are 0.158–44.59 kg CO2-eq and 3.3–154.4 MJ, respectively. (2) There are significant differences in GWP and CED during the life cycle of LIBs recycling with different battery types, shapes, recycling processes, and electric sources. Compared with NCM batteries, the GWP and CED of recycled LFP batteries are higher. The combined hydro-pyrometallurgical process performs the best for GWP and CED, while the pyrometallurgy is the worst. The GWP of LIBs recycled by Chinese electricity is the highest, and the CED of LIBs recycled by American electricity is the highest. (3) Among the influencing factors, cascade utilization contributes the most. Highlights: Meta-analysis is firstly used for evaluating the GWP and CED of LIBs recycling. The GWP of recycling one-kilogram LIBs is 0.158–44.59 kg CO2-eq . The CED of recycling one-kilogram LIBs is 3.3–154.4 MJ. The combined hydro-pyrometallurgical process performs the best. The dominant factor influencing GWP and CED is cascade utilization.